2018
DOI: 10.1128/genomea.00416-18
|View full text |Cite
|
Sign up to set email alerts
|

First Complete Genome Sequence of Yersinia massiliensis

Abstract: Using a combination of Illumina paired-end sequencing, Pacific Biosciences RS II sequencing, and OpGen Argus whole-genome optical mapping, we report here the first complete genome sequence of Yersinia massiliensis. The completed genome consists of a 4.99-Mb chromosome, a 121-kb megaplasmid, and a 57-kb plasmid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The association of Y. massiliensis , originally described as free living and non‐pathogenic (Merhej et al, 2008; Thomas et al, 2018), was already reported in A. nitens in Brazil (Ribeiro et al, 2022). Erwinia amylovora , from the gut microbiota of A. nitens , is the second report of this bacterium associated with an insect after being reported in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) (Anusree Padmanabhan et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…The association of Y. massiliensis , originally described as free living and non‐pathogenic (Merhej et al, 2008; Thomas et al, 2018), was already reported in A. nitens in Brazil (Ribeiro et al, 2022). Erwinia amylovora , from the gut microbiota of A. nitens , is the second report of this bacterium associated with an insect after being reported in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) (Anusree Padmanabhan et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…The Y. massiliensis DNA sequencing from the primer developed for the endosymbiont Arsenophonus may be due to the amplification of the 23S gene region in a non-specific way (Rekha et al, 2006). Yersinia massiliensis was originally described as a freshwater free-living gramnegative coccobacillus (Merhej et al, 2008) and has been found in aquatic and food environments in Brazil and Argentina (Souza et al, 2011) as non-pathogenic (Thomas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%